Scutellarin Attenuates the IL-1β-Induced Inflammation in Mouse Chondrocytes and Prevents Osteoarthritic Progression - Luo, Zucheng; Hu, Zhichao; Bian, Yujie; Su, Wenting; Li, Xiaoyang; Li, Shi; Wu, Jianbin; Shi, Li; Song, Yonghuan; Zheng, Gang; Ni, Wenfei; Xue, Jixin (Frontiers in Pharmacology, 2020)
Osteoarthritis (OA) is a type of joint disease that is characterized by the degradation and inflammation of articular cartilage. Scutellarin (SCU) is a flavonoid glycoside and is known to possess various biological and pharmacological activities including anti-inflammatory effects, which have been reported in various previous studies. Nevertheless, the effects of SCU on OA have not been explicitly elucidated. In the present study, we aimed to assess the effect of SCU on mouse OA chondrocytes. In vitro, the protein and mRNA expression levels of proinflammatory factors and matrix proteins such as matrix metalloproteinase-13 (MMP-13), a disintegrin and metalloproteinase with thrombospondin motifs 5 (ADAMTS-5), cyclooxygenase-2 (COX-2), and inducible nitric oxide synthase (iNOS) after treatment were measured by qRT-PCR and western blotting, respectively. The degradation of aggrecan and collagen II was reversed by SCU, and SCU inhibited the phosphorylation of the nuclear factor kappa B (NF-κB) and nuclear factor (erythroid-derived 2)-like 2 (Nrf2) signaling pathways both in vivo and in vitro. In vivo, a mouse OA model of destabilization of the medial meniscus (DMM) was established by intraperitoneal injection to evaluate the effect of SCU. Our experimental results indicate that SCU is a promising therapeutic approach for the treatment of OA.